Yūsuf Al-Qarḍāwī's Istinbāṭ Method and Its Implementation in the Moderation of Islamic Law - Ainol Yaqin (Al-Ahkam, 2021)
This paper described the formulation of Yūsuf al-Qarḍāwī's isntinbāṭ method towards moderate fiqh. The choice of this theme was based on the existence of two demeanours in religion, between permissive and inclusive. Two main questions in this research were, first, how did Yūsuf al-Qarḍāwī formulate the istinbāṭ method for moderate fiqh? Second, how is the implementation of this method in formulating Islamic law? This paper concluded two things through a literature study with the descriptive-analytic method. First, there were six formulations of the istinbāṭ method for the moderation of Islamic law. a. Examining the maqāṣid contained in the text before determining Islamic law, b. Linking texts and Islamic law with texts and other Islamic laws. c. Understanding texts in the frame of asbāb (al-nuzūl or al-wurūd), both micro and macro. d. Distinguishing between constant maqāṣids and changing instruments. e. Adjusting between al-thawābit and al-mutaghayyirāt. f. Observing the difference between worship and mu’āmalah in terms of wisdom, ‘illah and maqāṣid. Second, this method of istinbāṭ could produce fiqh with a flexible, elastic, dynamic, adaptive, and easy-to-practice.